2006
DOI: 10.1155/2006/357259
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Patients Are at Greater Risk of Cytopenia During Antiviral Therapy for Hepatitis C

Abstract: Elderly patients with chronic HCV can be treated successfully. However, they are more at risk to develop cytopenias while on treatment. In such patients, the close monitoring of blood counts is necessary. Larger studies are needed to confirm these findings and to determine whether SVR differs in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 15 publications
4
38
1
1
Order By: Relevance
“…They respond to therapy in the same manner as do those with elevated ALT (13). Older patients can be treated successfully (14).…”
Section: Contraindicationsmentioning
confidence: 96%
“…They respond to therapy in the same manner as do those with elevated ALT (13). Older patients can be treated successfully (14).…”
Section: Contraindicationsmentioning
confidence: 96%
“…Dose reduction or treatment discontinuation may lower the SVR and result in 10-20% reduction in the patients' adherence to the treatment regimen (14). The higher rate of cytopenia in adults, mainly in the elderly, can be explained by their lower level of baseline hemoglobin and neutrophil and platelet counts (15). Some authors have suggested that severe cytopenia is a marker for increased tumor-necrosis-factor (TnF) activity in patients, and this increased TnF activity translates into higher SVR (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, interferon therapy poses many challenges in elderly patients and those with advanced liver disease because of limited efficacy, safety, and tolerability [11]. Adverse effects, such as hemolytic anemia, are exacerbated in older patients [17][18][19][20][21]. Elderly patients are more likely to have concomitant comorbidities particularly metabolic (P \ 0.001) [11] and cardiovascular (P \ 0.001) [11] disease, along with renal, pulmonary, and hematologic conditions that prevent the use of PegIFN and RBV [22].…”
Section: Introductionmentioning
confidence: 99%